QTips - Lesbian Gay Bisexual Transgender Center (Tufts Archival Research Center, 2022)
Content Warning: This issue contains a front-page article describing acts of homophobic and anti-Asian harassment in the form of graffiti. The text of the graffiti is quoted with censored slurs. For more information on TARC's content warning policy please visit our website: https://tarc.tufts.edu/content-warnings-protocol-for-digital-archival-material.